Electrical Modification of Combustion and the Affect of Electrode Geometry on the Field Produced. (25th July 2011) - Dolmansley Dolmansley, Timothy J. C. Timothy J. C.; Wilson Wilson, Christopher W. Christopher W.; Stone Stone, David A. David A.
Abstract : There has been extensive work to show how electric fields can influence combustion. However, many different set ups are used. This work shows how different set ups produce different field strengths and that the field is not always uniformly distributed. The field strength is modelled using Ansys Maxwell. The type of material used is discussed and the set up of apparatus. It is recommended to use parallel plates for experimentation. Parallel plates produce the most uniform field this allow's it's influence to be directly investigated and related to the field strength.